2020
DOI: 10.1111/ina.12645
|View full text |Cite
|
Sign up to set email alerts
|

Comparing regional stove‐usage patterns and using those patterns to model indoor air quality impacts

Abstract: Monitoring improved cookstove adoption and usage in developing countries can help anticipate potential health and environmental benefits that may result from household energy interventions. This study explores stove-usage monitor (SUM)-derived (38 stoves, 1007 monitoring days). Traditional stove usage was found to be generally similar among four seemingly disparate countries in terms of cooking habits, with average usage of between 171 and 257 minutes per day for the most-used stoves. In Honduras, where survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…The model also overestimates the measured kitchen concentrations (~10‐fold for PM 2.5 ) and (~6‐fold for CO). This bias is similar to what was reported by Piedrahita et al 42 and Johnson et al, 43 who both found the model to overestimate measured concentrations in the kitchen. There are several reasons for this potential bias, the most likely being due to the model assumptions that all emitted pollutants instantaneously and perfectly mix throughout the room.…”
Section: Resultssupporting
confidence: 90%
“…The model also overestimates the measured kitchen concentrations (~10‐fold for PM 2.5 ) and (~6‐fold for CO). This bias is similar to what was reported by Piedrahita et al 42 and Johnson et al, 43 who both found the model to overestimate measured concentrations in the kitchen. There are several reasons for this potential bias, the most likely being due to the model assumptions that all emitted pollutants instantaneously and perfectly mix throughout the room.…”
Section: Resultssupporting
confidence: 90%
“…The DHS data do not include information on other or secondary cooking fuels in the household. Some households reported using more than one fuel, which would lead to misclassification in the exposure definition and bias the estimated associations [ 41 ] The study did not include information on ambient air pollution, which may also be associated with high blood pressure. There was little or no information on the use of blood pressure medication.…”
Section: Discussionmentioning
confidence: 99%
“…Given the extra asset costs associated with a PAYG model, monitoring of multiple years of cooking patterns under such model is needed to understand its ability to sustain use of LPG over time. Previous studies containing objective stove use measurements have typically utilized temperature sensors [35] , [36] , with the temperature data being dichotomized into ‘stove use’ or ‘non-use’ using advanced algorithms [37] , including machine learning [38] . PAYG LPG smart meter technology has the advantage of real-time recording of the quantity (kilograms) of LPG consumed and length of time the smart meter was in use.…”
Section: Introductionmentioning
confidence: 99%